Training of Personnel for the Internal Affairs Agencies of the Ukrainian SSR at the Turn of the 1960s and 1970s. (Law and Safety, 2025)
The article examines the main aspects of recruitment, training and education of militia personnel in 1969–1970. The staffing of the Ukrainian SSR militia in this period can be considered satisfactory, but the situation with their qualitative composition, the level of special and higher education, advanced training of these personnel, the level of their combat and physical training was not satisfactory enough. As of the beginning of 1970, a certain part of the senior staff of the internal affairs bodies did not even have a general secondary education. There was a considerable lag in raising the educational level of employees in the criminal investigation, departments for combating the theft of socialist property and the State Automobile Inspectorate. The number of officers with higher education in these services increased extremely slowly and amounted to 15.2 % in the criminal investigation department, 21.0 % in the departments for combating the theft of socialist property, and 9.3 % in the State Automobile Inspectorate. At the beginning of 1970, every second police officer in the republic did not have a general secondary education, and in the departments of internal affairs of Ivano-Frankivsk, Rivne, Lviv, Ternopil, and Kherson regions, the number was up to 75 %. These were very low figures, which could not but affect the efficiency of these units. In many regional internal affairs departments, training sessions were held irregularly and in a poorly organised manner. Many militia employees were not able to shoot accurately, did not know the grounds for using weapons, and did not know sambo techniques. There were few group exercises and operational training sessions to teach officers how to conduct multidimensional preventive work, solve crimes in hot pursuit, and organise the search for and detention of dangerous criminals. The training of district inspectors did not sufficiently use the best practices of the best district inspectors. There were significant shortcomings in the organisation of initial training for newly recruited police officers. The Ministry of Internal Affairs of the Ukrainian SSR tried to improve this situation by considering this issue at its board, emphasising it in special directives and instructions, but despite this, no positive changes were actually achieved in 1969–1970. The leadership of the Ministry of Internal Affairs tried to improve the conditions of service in the militia, to make it more attractive and prestigious in order to retain personnel. To this end, uniforms were improved, and the awarding of the badge “Distinguished Militia Officer” was restored.
Keywords: Ukraine; 1960s–1970s; Ministry of Internal Affairs; militia; personnel.